Judge’s Considerations Analysis toward Perpetrators of Criminal Acts of Sexual Violence to Underage Children in Demak District Court Reviewed with Law Number 35 Year 2014 about Children Protection - Sri Endah Wahyuningsih; Muhammad Sholeh (Jurnal Pembaharuan Hukum, 2017)
The welfare of every Indonesian citizen is guaranteed in every their right including the children protection rights which is included as human right. To achieve the protection and welfare of the child, the government issued Law Number: The existence of Law Number 35 Year 2014 on the Amendment of Law Number 23 Year 2002 regarding Children Protection affirms the need for criminal sanction penalty and fines for perpetrators of crimes against children, especially to a sexual crime that aims to provide a deterrent effect, and encourages concrete steps to restore the physical, psychological and social life of the child. The research was conducted at the Demak District Court. This is kind of sociological juridical research, which examines the application of sanctions of sexual violence committed against adults at the Demak District Court. The result of the research shows that the judge of Demak District Court in applying criminal sanction is guided by Law no. 35 Year 2014. Penal sanctions, this is fair for both the public and the justice seeker itself. Judge's consideration in imposing a criminal sanctions imprisonment, is based on the defendant being polite in the court, admitting to the truth and regretting his actions.